Telitacicept as a novel B cell-targeted therapy in autoimmune encephalitis: a case report - Jiang, Zhishan; Liang, Huafeng; Chen, Sheng; Zhou, Qinming (Frontiers in Immunology, 2025)
Autoimmune encephalitis (AE) comprises immune-mediated neuroinflammatory disorders presenting diverse neuropsychiatric symptoms and antibody-specific manifestations. Despite standard immunotherapy, residual disability, treatment intolerance, and relapse risks highlight unmet clinical needs. Telitacicept, a dual target fusion protein that inhibits B-lymphocyte stimulator (BLyS) and a proliferation-inducing ligand (APRIL), suppresses pathogenic B cell activation and autoantibody production, presenting a mechanism-driven therapeutic potential for AE management. Three AE cases with distinct therapeutic complexities are detailed in our study: (1) An anti-N-methyl-D-aspartate receptor (NMDAR) antibody-positive patient experienced recurrent relapses and was a comorbid individual with upper gastrointestinal bleeding. (2) An anti-leucine-rich glioma inactivated 1 (LGI1) antibody patient resisted corticosteroids, intravenous immunoglobulin, and ofatumumab treatment. (3) A newly diagnosed, anti-LGI1 antibody and anti-contactin-associated protein 2 (CASPR2) antibody dual-positive patient required sequential therapy to consolidate the remission and facilitate prednisone tapering. Telitacicept administration achieved symptom remission across all cases, accompanied by reduced antibody titers and stable outcomes over six months. Our case series evaluates the use of telitacicept in AE patients with varied antibody subtypes, particularly for patients with relapsed or refractory disease, intolerance to CD20-targeted agents, or steroid-related complications. Moreover, telitacicept may serve as an effective sequential therapy to sustain remission and reduce long-term steroid dependency.